2021
DOI: 10.21037/jtd-21-765
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning methods for perioperative anesthetic management in cardiac surgery patients: a scoping review

Abstract: Background: Machine learning (ML) is developing fast with promising prospects within medicine and already has several applications in perioperative care. We conducted a scoping review to examine the extent and potential limitations of ML implementation in perioperative anesthetic care, specifically in cardiac surgery patients. Methods: We mapped the current literature by searching three databases: MEDLINE (Ovid), EMBASE (Ovid), and Cochrane Library. Articles were eligible if they reported on perioperative ML u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…Although interpretable models are frequently preferred even among experts, machine learning models are increasingly popular. 43 Some reports suggest better performance for ML models compared to traditional clinical scoring systems, 17,18 but few have been validated on multiple external datasets. We evaluated five of the most commonly used methods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although interpretable models are frequently preferred even among experts, machine learning models are increasingly popular. 43 Some reports suggest better performance for ML models compared to traditional clinical scoring systems, 17,18 but few have been validated on multiple external datasets. We evaluated five of the most commonly used methods.…”
Section: Discussionmentioning
confidence: 99%
“…The conservative 0.7 minimum acceptance threshold for AUC was based on consultation with clinical advisors and a literature review indicating the acceptability of numerous perioperative machine learning models with c-statistics in the 0.7 to 0.8 range. 18,30 Because no a priori hypotheses were tested, we did not estimate required sample size, and instead used all eligible cases available in the Medicare fee-for-service files for the selected years. To evaluate the importance of endpoint-specific models, we compared incidence of various complications in patients selected for having the highest 5% risk of 90-day mortality to those with the highest 5% risk of specific complications.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Many predictive models significantly increase in accuracy with increased data, 19 thus complex full-waveform data streams, such as intraoperative electroencephalogram (EEG) signals, heart rate, blood pressure, and end-tidal Co 2 , have been increasingly used as model inputs. [20][21][22] Real-time data streams also make possible closed-loop control systems to assist with patient care, such as titration of sedation or vasopressors. 23 Because of the challenge of complex artificial intelligence (AI) models to perform well across different institutions and time periods, traditional statistical models still have a role and can sometimes outperform deep learning models.…”
Section: Predictive Models For Perioperative and Critical Carementioning
confidence: 99%
“…Proper prognostication of postoperative morbidity and mortality would be informative, precluding overestimation of risk and denial of surgery for patients deserving it, which could occur with some prediction models due to the high prevalence of comorbid conditions in an elderly individual. A short length of stay after cardiac surgery was correlated with younger age, no preoperative use of beta-blockers, shorter cross-clamp time, and absence of congestive heart failure showed that GA by applying GA can produce better predictivity in medicine [29].…”
Section: Surgerymentioning
confidence: 99%